The Algerian, Tunisian And Moroccan Press: Historical And Linguistic Issues (Journal of Namibian Studies : History Politics Culture, 2023)
This article offers a comprehensive overview of the development of print media in the Maghreb countries, focusing mainly on Algeria, Morocco, and Tunisia and their use of the French language. It delves into the origins, historical, political, and socio-cultural influences shaping the press in each country while addressing challenges such as censorship, financial constraints, and competition from electronic media at various times. Additionally, this contribution highlights the impact of different political periods, especially post-independence and revolutions, and the evolution of partisan press in these contexts. The role of the French language in the press is also discussed, emphasizing its significance as a lingua franca in the Maghreb region and its role in disseminating ideas despite efforts to promote national languages.